Annihilating Space and Time: The Modernization of Fire-Fighting in Late Nineteenth-Century Cornwall, Ontario - Stein, Jeremy (Urban History Review / Revue d'histoire urbaine, 1996)
The concept "time-space convergence" is rarely used in the context of internal urban communication or urban service provision. This paper applies the concept to the process and modernization of fire-fighting. It does so with reference to Cornwall, Ontario's experience of fighting fires in the late nineteenth century. Examination of the fire-fighting process and of technology's historical role within it shows "time-space convergence" to be a pervasive feature of urban fire control Evidence from Cornwall supports this assertion. Speed was critical. The advent of manufacturing, the wish of Cornwall's elite to protect its property, and greater emphasis on the economic value of time and space, all contributed to renewed efforts to speed up the process of fighting fires. Repeatedly, these concerns prompted decisions to invest in new fire-fighting technology. Success was limited, but communities like Cornwall came increasingly to view technology as a measure of their modernity and communal worth. Acquisition of new fire-fighting technology was a clear demonstration of a community's intention to protect accumulated urban assets. This demonstration of intent was as much evidence of a community's modernity as were the multiple efforts to demonstrate and to improve upon the technology's effectiveness.